1999
DOI: 10.1109/77.783784
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical results of electromagnetic nondestructive testing with HTc SQUIDS

Abstract: International audienceWe present here recent results on detection of surface and subsurface artificial features in Al-Ti planar structures, to show current performance of our eddy-current nondestructive evaluation system based on HTc SQUIDs. The anomalous magnetic fields generated by flaws with known electromagnetic characteristics have been modeled by three-dimensional codes based on finite element method and volume integral formulation and developed for the investigated problem. Both numerical solutions have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Weinstock et al [26] tested NbTi/Cu wires for defects using an HTS dc SQUID. A field which has been widely explored is nondestructive testing of aircraft parts using eddy current techniques, for eample, by Wikswo [27], Hohmann et al [28], Kreutzbruck et al [29], Ruosi et al [30], and Tavrin et al [31]. Finally, pre-stressed concrete bridge structures have been tested by Krause et al [32] making dc measurements of the remanent magnetization of the steel reinforcement with a portable HTS SQUID.…”
Section: Flux Guidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Weinstock et al [26] tested NbTi/Cu wires for defects using an HTS dc SQUID. A field which has been widely explored is nondestructive testing of aircraft parts using eddy current techniques, for eample, by Wikswo [27], Hohmann et al [28], Kreutzbruck et al [29], Ruosi et al [30], and Tavrin et al [31]. Finally, pre-stressed concrete bridge structures have been tested by Krause et al [32] making dc measurements of the remanent magnetization of the steel reinforcement with a portable HTS SQUID.…”
Section: Flux Guidesmentioning
confidence: 99%
“…As usually users of NDE systems are not much interested in the current flow in the sample, but rather want to find defects, this is not a big disadvantage. In order to minimize the excitation field at the location of the SQUID, a gradiometric excitation coil (a so-called double-D coil, see, e.g., [28][29][30]) can be used. By carefully moving this coil below the SQUID to find its optimum position, the cross talk between excitation coil and SQUID can be kept lower than 0.1%.…”
Section: Excitation Of (Eddy) Currentsmentioning
confidence: 99%
“…Secondary field In a series of studies [1][2][3], a double-D coil was employed as exciting coil, in our study; however, it was used as a pickup coil. A double-D coil, which is simply made from two semicircular wires connected in counter-series, is placed so that it is coplanar and coaxial with the exciting ring coil within which it is contained, as can be seen in Fig.…”
Section: A(r Z)mentioning
confidence: 99%
“…Although there have been many studies of ECT based on the use of a double-D coil e.g., [1][2][3], it has mostly been used as an excitation coil, and the studies have generally reported experimental modeling and its results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation